Problematic usage, safety knowledge, and dependency challenges of mobile phones among late adolescents in southern India: a mixed-methods study - Akshay, Parambilankandi; Olickal, Jeby Jose; Roy, Durgesh; Jayaseelan, Venkatachalam; Thulasingam, Mahalakshmy; V. P., Renu (International Journal Of Community Medicine And Public Health, 2024)
Background: Globally, the number of people using mobile phones is estimated to be around 8.1 billion, with the majority being youths. Therefore, our aim was to assess problematic mobile phone use among late adolescents. Methods: We conducted an exploratory mixed-method study among selected schools in Puducherry, South India, from September to October 2019. Two focus group discussions (FGDs) were held among students exhibiting high problematic mobile phone use. Results: A total of 498 students were enrolled, with a mean (SD) age of 14.3 (1.4) years, and more than half were male. Approximately 77% reported using mobile phones, with around 30% spending more than one hour per day on mobile use. Of the total, 23% (95% CI 19.3-26.8) exhibited problematic mobile phone use. Factors significantly associated with problematic use included the student's level of education (APR= 5.6, 95% CI 1.3 – 24.7), parents' occupations (APR= 3.8, 95% CI 1.2 – 12.2), and hours spent on mobile phones (APR= 2.1, 95% CI 1.3 – 3.4). Only 50% were aware that increased mobile phone use is harmful. Qualitative interviews provided significant insights into smartphone dependency and challenges faced by students. Conclusions: There is a pressing need for comprehensive initiatives to promote responsible smartphone use.